Pengembangan metode bioasesmen untuk penilaian kualitas air Sungai Cihampelas di DAS Citarum - Aiman Ibrahim; Achmad Sjarmidi (JURNAL SUMBER DAYA AIR, 2017)
Cihampelas Stream is a tributary of the Citarum that flows across the Regency and Bandung area along 8,5 km. Cihampelas Stream are utilized by the community for domestic activities, tourism, agriculture, and fisheries. This study aims to determine the water quality based on Macrozoobenthos Index of Biotic Integrity and Periphytic Diatom Index of Biotic Integrity and its correlation with the Pollution Index (water classes). This research was conducted at four Cihampelas Stream stations representing the minimal areas of disturbance to the predicted areas of disturbance such as Cilengkrang, Cisurupan, Pasanggrahan, and Mekarmulya. Water sampling, macrozoobenthos, and periphytic diatom was conducted from July to September 2016 four times at two-week intervals. Assessment of water quality using Macrozoobenthos Index of Biotic Integrity shows that Cihampelas Stream is categorized from very good to bad category with index value ranging from 4?18. The water quality of the Cihampelas Stream shows very good to bad category based on the value of the Periphytic Diatom Index of Biotic Integrity which ranges from 3?15. Based on Pollution Index, along Cihampelas Stream is fulfilled class I to exceed class IV of water quality standard. Spearman correlation analysis results shows that Pollution Index (water classes) has negative correlation and stronger to Macrozoobenthos Index of Biotic Integrity compared to Periphytic Diatom Index of Biotic Integrity.Development of bioassessment methode for water quality assessment of Cihampelas Stream in the Citarum River Basin